Pengembangan Media Pembelajaran Powerpoint Berbasis Model Inquiry Pada Pembelajaran Tematik Terpadu Di Kelas IV Sekolah Dasar - Rossa, Rona; Kurnia Sapitri, Aprilia (LP2M Universitas Adzkia, 2023)
This research was motivated by several problems, namely learning only using textbooks and delivering material using the lecture method. Based on these problems, an inquiry model-based powerpoint learning media was developed in integrated thematic learning in grade IV elementary schools on theme 3 sub-themes 1 learning 1 and 2. This research was conducted at SDN 19 Sitiung, Dharmasraya Regency. The purpose of this research is to produce valid, practical and effective learning media. The type of this research is research and development (R&D) using a 4-D model (define, design, development, disseminate. The data collection instrument in this study is a learning media validation sheet (for design, language, and material experts), practicality tests, and effectiveness test.The results of the validation test for developing PowerPoint learning media based on the Inquiry model with 4 validators were categorized as very valid, the results from the practicality test by one educator and eleven students were categorized as very practical, and the results of the effectiveness test by eleven students were categorized as very The level of validity obtained by the results of the validity test is the percentage of design feasibility (90.6%), language percentage (85%), material percentage 1 (91.6%) and material percentage 2 (93.3%). by educators get an average value (100%) and practicality test by students get an average value (100%).The results of the effectiveness test of the eleven students scored in learning 1 (93.6%) and learning 2 (92.7%). Proving that the development of PowerPoint learning media based on the Inquiry model in integrated thematic learning in grade 4 SD theme 3 sub-theme 1 learning 1 and 2 is declared valid, practical, effective and feasible to use. The advantages of this product are that it can attract the attention of students, increase students' understanding of the material, and encourage students to be active in learning